Towards the establishment of collaboration between the Ramon Magsaysay (Cubao) High School Library and the Quezon City Public Library - Diaz, Chad Aren E.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
Helping provide a functionally-literate society is one of the ultimate goals of both school and public libraries. However, realization of the said goal is hindered by the different issues the libraries face such as inadequate resources and budget, poor library services, and absence of a licensed librarian. Collaboration, the act of working together that includes establishment of joint goal and vision, is seen as an answer to address the said issues, hence, helping school and public libraries improve.
This study aimed to determine the possibility of establishing collaboration between the Ramon Magsaysay (Cubao) High School Library and the Quezon City Public Library Cubao and Main Branches. Questionnaires were administered to the students, teachers and school librarians/teacher-librarians of RMCHS and public librarians (which include professional and para-professional staff) of the two branches of QCPL. Interviews were conducted with the principal and the head librarian of the 3 institutions. There were a total of 204 respondents for this study.
Results of the study showed that the heads of each institution were in favor of undergoing collaboration and the public librarians were generally aware of the existence of a standard mandating school and public library to collaborate. It was also revealed that there exists a great need to undergo collaboration and that such action will provide more advantages than disadvantages. The respondents also shared that they have unique roles to play in collaboration, namely, leaders, facilitators and users. Networking and resource sharing were favored by the respondents to be the activities that should be implemented first under collaboration and that funds for this activity should generally come from the government. Lastly, it was found out that meetings will play a crucial role in communication among key members in order for them to produce a mutual partnership with good relationship towards each other. Interviews done revealed that the principal and both the head librarians of QCPL Main Branch and Cubao Branch are in-favor of library collaboration and recognize the role of libraries in making a literate society.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Ramon Magsaysay (Cubao) High School Library; Quezon City Public Library; Library cooperation -- Philippines -- Quezon City